2020
DOI: 10.1002/ces2.10040
|View full text |Cite
|
Sign up to set email alerts
|

Review of thermo‐kinetic correlation during grain growth in nanocrystalline materials

Abstract: Nanocrystalline (NC) materials exhibit many unique properties over their coarse‐grained counterparts due to the high grain boundary density and the small grain size, but they are too difficult to be used in engineering environment because of the poor thermal stability. With regard of this, two strategies are previously proposed to enhance the thermal stability (or impede the grain growth) of NC materials, that is, the thermodynamic and the kinetic approaches. Recent investigations increasingly support that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 100 publications
(243 reference statements)
1
11
0
Order By: Relevance
“…10,[13][14][15] Specifically, dopants can extend the stability of single phase regions in the diagram, a phenomenon fundamentally related to the stabilization of interfaces (i.e., interfacial energy lowering). 15 This phenomenon has been observed in various doped nanocrystalline oxide systems, and it is possible Al 3+ ion enrichment at the interfaces may affect Y 2 O 3 densification. 11,[16][17][18][19] Wang et al studied the role of Al 2 O 3 on the sintering of Y 2 O 3 containing small amounts of Tm and Zr.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…10,[13][14][15] Specifically, dopants can extend the stability of single phase regions in the diagram, a phenomenon fundamentally related to the stabilization of interfaces (i.e., interfacial energy lowering). 15 This phenomenon has been observed in various doped nanocrystalline oxide systems, and it is possible Al 3+ ion enrichment at the interfaces may affect Y 2 O 3 densification. 11,[16][17][18][19] Wang et al studied the role of Al 2 O 3 on the sintering of Y 2 O 3 containing small amounts of Tm and Zr.…”
Section: Methodsmentioning
confidence: 99%
“…The diagram indicates that even at low Al 3+ ion concentration, Al‐rich eutectic monoclinic Y 4 Al 2 O 9 phase is formed along with Y 2 O 3 , suggesting that the second phase formation is more energetically favorable than the formation of solid solution in Al‐doped Y 2 O 3 12 . However, bulk phase diagrams do not take interfacial energies into consideration, while it has been demonstrated that the high interface to volume ratio in nanoscale materials can lead to non‐negligible interfacial energy contributions to the phase diagram, deviating it from bulk equilibrium values 10,13–15 . Specifically, dopants can extend the stability of single phase regions in the diagram, a phenomenon fundamentally related to the stabilization of interfaces (i.e., interfacial energy lowering) 15 …”
Section: Introductionmentioning
confidence: 99%
“…In general, at the nanoscale, properties and processes, such as fracture toughness, reactivity, phase transitions, and coarsening, are strongly dependent on interfacial characteristics. In particular, interfacial energies, which include both solid–vapor (surface) and solid–solid (grain boundaries, resulting from aggregation or partial sintering), are key parameters controlling coarsening, phase equilibrium, and other physical properties . For instance, the stability of MgAl 2 O 4 as a catalytic support is strongly affected by its surface energy, and the material shows improved resistance to coarsening when the surface energy is lowered by the addition of dopants .…”
Section: Introductionmentioning
confidence: 99%
“…As a novel strategy to manipulate the functional properties of nanomaterials, Hasan et al demonstrated by atomistic simulations and experiments (calorimetry) that surface energies of MgAl 2 O 4 can be reduced by using dopants prone to segregation. , The segregation was in fact a spontaneous formation of surface excess where trivalent dopants substituted Al 3+ at the surfaces, leading to a surface energy decrease due to a better satisfied coordination of local ions. While all surface energies were generally reduced, some surface planes were affected more strongly than others, resulting in an increase in the fraction of the (111) surface .…”
Section: Introductionmentioning
confidence: 99%
“…However, in systems composed of random-sized nanoparticles with a high surface area it becomes even harder to predict the sintering mechanisms. It is proposed that a thermokinetic correlation considering both interfacial energies and diffusion coefficients define the sintering mechanisms of densification or non-densification [136,137].…”
Section: Sinteringmentioning
confidence: 99%